Recurrent laryngeal papillomatosis: successful treatment with human papillomavirus vaccination. Issue 5 (10th January 2011) - Mudry, Peter; Vavrina, Martin; Mazanek, Pavel; Machalova, Michaela; Litzman, Jiri; Sterba, Jaroslav
Abstract : The authors describe the case of a 5-year-old girl with recurrent laryngeal papillomatosis (RLP) due to human papillomavirus (HPV) type 11, who required frequent surgical treatment. Complete recovery occurred after HPV vaccination (Gardasil). Confirmed remission of RLP has continued during the 17 months of follow-up since vaccination. The authors conclude that HPV vaccination may represent a new therapeutic option in this situation.